INTEGRASI ILMU AGAMA DAN SAINS DI PERGURUAN TINGGI TERHADAP PENDIDIKAN ISLAM DI ERA MODERN - Nur Hasanah Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
This article discusses the importance of integrating religious knowledge and science to enhance the quality of Islamic education, particularly in the modern era. This approach not only broadens students' understanding by combining religious teachings with scientific knowledge but also contributes to character development, ethics, and the relevance of Islamic education itself. Graduates of Islamic education programs that integrate both fields possess a competitive edge in the professional world, as they are not only knowledgeable in religious studies and science but also equipped with strong moral values to apply their knowledge responsibly. However, the implementation of this integration faces several challenges, such as resistance from some segments of society, limitations in the curriculum, and a lack of teacher training. The article also emphasizes the importance of the role of educators and the design of an integrated curriculum to achieve Islamic education that aligns with modern developments. The positive impact of this integration is also felt by society, producing individuals who can use scientific knowledge to improve social and environmental conditions while adhering to religious principles. Therefore, the integration of religious knowledge and science not only enriches students' understanding but also elevates the overall quality of Islamic education for both worldly and spiritual life.